STUDY OF THE TECHNOLOGICAL SCHEME OF TOMATO PASTE DRYING AND SAFETY CONTROL ACCORDING TO THE PRINCIPLES OF HACCP - ZUBKOVA, KATERYNA; STOYANOVA, OLHA; SHERSTIUK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Drying fruits and vegetables is a process in which the removal of moisture stops the activity of microorganisms that cause spoilage, as well as the activity of enzymes, thus preserving the structure, organoleptic characteristics and nutritional value of the raw material. The conditions of drying and grinding during processing of powders strongly influence the qualitative characteristics of biological materials. Ensuring the quality of vegetable powders requires constant improvement of appropriate drying technologies, which will allow to significantly reduce the duration of processing and improve the quality of the finished product. Solving the problem of tomato powder production is possible by improving the technological scheme and drying by spraying. The main advantage of a vacuum-type dryer is the high quality of the finished product when drying heat-sensitive, easily oxidized raw materials. The paper proposes a technological scheme for drying tomato paste by the spray method to obtain a powder with improved consumption properties, due to the preservation of vitamins, valuable macro- and microelements. A block diagram of the control of the manufacturing process and the HACCP plan (analysis and control of hazardous factors) of tomato paste powder with the establishment of control and control-critical points on it are given, which allow to fully control the entire process of the production of a safe food product in accordance with the principles of HACCP. The main advantage of a vacuum-type dryer is the high quality of the finished product. Dehydration of tomato paste granules, taking into account the maximum preservation of valuable nutrients in the product at different coolant temperatures, led to the high quality of the finished product.